Trauma-Induced Double-Seronegative Ocular Myasthenia Gravis: A Case Report - Khalid, Mohammad Ali; Awan, Muhammad Jawad; Gull, Ambreen; Hafeez, Nida; Ali, Bushra; Niazi, Fuad Ahmad Khan (Journal of Rawalpindi Medical College, 2024)
We present here a 12-year-old child who presented with complaints of blurring of vision and drooping of the left upper eyelid for the past 4 years, which started 1 month after he encountered blunt trauma to the left-sided orbital region. History, examination and pharmacological (neostigmine test) tests were suggestive of ocular myasthenia gravis, however anti-acetylcholine receptor antibodies and anti-musk antibodies were negative. Repetitive nerve stimulation tests and electromyography were also unremarkable. The patient was labelled as a case of trauma-induced double-Seronegative Ocular Myasthenia Gravis and was started on oral Pyridostigmine. The patient reported a drastic improvement in both diplopia and ptosis that he initially presented with. Ocular Myasthenia Gravis can be a diagnostic challenge as its initial presentation can vary to a great degree. Thorough history and examination remain of prime importance which can provide adequate clues to lead us to the diagnosis of ocular myasthenia gravis. Trauma should also be recognized as a triggering factor for myasthenia gravis and more attention needs to be given to understand the pathophysiology of this interesting association.